Development of Multimedia-Based Teaching Materials to Improve Mathematical Communication Skills in the Context of Statistical Literacy - Andrianingsih, Vivi; nurramdaniyah, Nurramdaniyah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This This study aims to develop multimedia-based teaching materials grounded in statistical literacy to improve students’ mathematical communication skills. The development process employed the ADDIE model. The quality of the product was determined based on three criteria: validity, practicality, and effectiveness. Validity was evaluated by experts using established feasibility standards (≥85% categorized as very valid), practicality was assessed through teacher and student responses, and effectiveness was measured using a paired-sample t-test supported by learning gain analysis. The results show that the developed multimedia achieved high validity (material expert = 87.5%, media expert = 93.5%, learning expert = 94.45%), indicating that the content, design, and pedagogy are appropriate for learning. Practicality results revealed positive responses from students (84.9%) and teachers (87.5%), suggesting that the multimedia is easy to use and supports classroom implementation. Furthermore, the effectiveness test showed a significant improvement in students’ mathematical communication skills (mean score increased from 62.19 to 84.46; p < 0.05), which is supported by an average N-gain score of 0.523, categorized as medium. This indicates that the integration of statistical literacy contexts within multimedia facilitates students in interpreting, representing, and communicating data meaningfully. These findings demonstrate that multimedia grounded in statistical literacy not only enhances student engagement but also supports the development of mathematical communication skills through contextual data interpretation processes.